1995
DOI: 10.1111/j.1365-2133.1995.tb08666.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumour necrosis factor alpha is pro-inflammatory in normal human skin and modulates cutaneous adhesion molecule expression

Abstract: Tumour necrosis factor alpha (TNF-alpha) is a potent immunoregulatory cytokine produced by many cutaneous cells, including keratinocytes, mast cells and Langerhans cells. To explore its potential role in inflammatory skin disease, we have studied immunohistochemically the effects of intradermal recombinant human TNF-alpha (rHuTNF-alpha) on cutaneous inflammatory cells, adhesion molecules and Langerhans cells in normal human skin. Volunteers receive rHuTNF-alpha 100 U (group A), 5000 U (group B), or 100 U daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(84 citation statements)
references
References 36 publications
3
80
0
1
Order By: Relevance
“…However, these findings are consistent with data from injection of IL-1 (11) or TNF (25) into normal human skin, either of which may result in recruitment of many macrophage-like cells. It seems likely that the persistent secretion of IL-1 into the dermis of these animals results in an adhesion molecule and secondary cytokine profile that results preferentially in the accumulation of monocytic cells.…”
Section: Discussionsupporting
confidence: 89%
“…However, these findings are consistent with data from injection of IL-1 (11) or TNF (25) into normal human skin, either of which may result in recruitment of many macrophage-like cells. It seems likely that the persistent secretion of IL-1 into the dermis of these animals results in an adhesion molecule and secondary cytokine profile that results preferentially in the accumulation of monocytic cells.…”
Section: Discussionsupporting
confidence: 89%
“…Our data, however, suggest a surprisingly dominant role for CCR6 and LARC in the acute arrest of mTC to activated dermal endothelium. Although ours is an vitro study, the proteins acutely expressed by TNF-␣-stimulated HDMEC in vitro closely parallel those expressed in vivo when human subjects were injected with TNF-␣ intradermally (25). Moreover, a recent report demonstrated that protein expression of CCR6 and chemotactic sensitivity to LARC are up-regulated in the T cells of psoriatic patients (15), which lends support to the possible importance of CCR6 in vivo.…”
Section: Resultsmentioning
confidence: 66%
“…2). TNF-␣ has been shown to cause depletion of epidermal Langerhans cells and recruitment of macrophages into the dermis, which are important events in the modulation of alloantigen presentation in human skin (47). The immunosuppressive effects of cis-UCA may be partially mediated via TNF-␣, because anti-TNF-␣ treated or TNF-␣ receptor knockout mice show a reduced cis-UCA induced suppression of the CHS response (9,11).…”
Section: Discussionmentioning
confidence: 99%